PERSEPSI MASYARAKAT TERHADAP PENGELOLAAN HUTAN DESA MIRE KECAMATAN ULUBONGKA KABUPATEN TOJO UNA-UNA - Adinda, Septiani Rima; Umar, Syukur; Maiwa, Arman (Universitas Tadulako, 2021)
Population Data in the village of Mire Ulubongka district as much as 1000 inhabitants. In the sampling taken where the number of families head is 275 head of the family is in the village of Mire.in Sampling research stating that if the sample is less than 100 then the sample should be taken in it’s entinety and if otherwise the sample is more than 100 then the sample is taken only 15%, 20%, or more. Based on the explanation above, Sample were taken by 42 head of the family (15%). The level understanding of the community in Mire Village towards forest management overall is high and some people in Mire village have not understood about the sustainable management of village forest, this is due to various factors, among others from the limited level of education, the lack of socialization and training on the management plan of Mire village forest, lack of knowledge on it’s principles, and community perceptions or responses are dominated by their hopes of increasing economic income through the management Mire Village Forests.Keywords: People Perception, Village Forest